2023
DOI: 10.3390/su15021228
|View full text |Cite
|
Sign up to set email alerts
|

Panic Buying Behavior Analysis according to Consumer Income and Product Type during COVID-19

Abstract: In 2020, just before measures were established by governments to minimize the spread of SARS-CoV-2, such as social distancing, quarantine, lockdowns, and internal movement restrictions, people began to buy some products in quantities much superior to their regular needs. This behavior is called panic buying and is a typical human response in times of crisis and uncertainty. This study compares retail sale levels during the period in which panic purchases occurred to the sales levels before and after that perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…The peak sales (dashed line) occurred in March 2021, as well as the peak in number of cases ( Figure 1c ) and deaths ( Figure 1d ) due to covid-19. On the other hand, Google ® searches ( Figure 1a ) and the number of tweets ( Figure 1b ) showed peaks in May 2020, still in the initial phase of the pandemic, indicating a similar behavior to panic buying 6 . This was mainly related to the euphoria of some world leaders, and chloroquine was introduced as an easy solution to the health crisis 23 .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The peak sales (dashed line) occurred in March 2021, as well as the peak in number of cases ( Figure 1c ) and deaths ( Figure 1d ) due to covid-19. On the other hand, Google ® searches ( Figure 1a ) and the number of tweets ( Figure 1b ) showed peaks in May 2020, still in the initial phase of the pandemic, indicating a similar behavior to panic buying 6 . This was mainly related to the euphoria of some world leaders, and chloroquine was introduced as an easy solution to the health crisis 23 .…”
Section: Resultsmentioning
confidence: 89%
“…Observa-se que o pico de vendas (série tracejada) ocorreu em março de 2021, assim como o pico de casos ( Figura 1c ) e de óbitos ( Figura 1d ). Por outro lado, as pesquisas no Google® ( Figura 1a ) e o número de tweets ( Figura 1b ) apresentaram picos em maio de 2020, ainda na fase inicial da pandemia, indicando comportamento similar ao de compras em pânico 6 . Isso está relacionado, principalmente, à euforia de alguns líderes mundiais e a apresentação da cloroquina como uma solução fácil para a crise sanitária 23 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Income is a superior determinant of purchasing behavior (Roszkowska-Hołysz, 2013;de Brito Junior et al, 2023). Mamat, Noor & Noor (2016) findings suggested that income of individuals does influence their luxury purchase intention.…”
Section: Incomementioning
confidence: 99%